Considerations about the Time: Bergson and Deleuze's contributions to performance studies (Urdimento: Revista de Estudos em Artes Cênicas, 2022)
This article proposes a way of looking at performance art through the lens of schizoanalysis. It addresses issues related to the understanding of Time as a continuous flow, based on the concepts of duration and becoming found in the works of Henri Bergson and Gilles Deleuze, taking as an object of analysis the performance Sometimes doing something leads to nothing by the Belgian artist Francis Alÿs. Starting from the notion of subjectivity as movement and creative activity as an affirmation of difference and life, the work discusses possible lines to think about aesthetic relations, also transversalizing them with the philosophies of Nietzsche and Spinoza, as well as other intercessors to weave their own considerations about Time in art and Time of art.
Keywords: Performance; Politics; Aesthetics; Body; Subjectivation processes